Optimal Timing to Surgery After Neoadjuvant Chemotherapy for Locally Advanced Gastric Cancer - Wang, Yinkui; Liu, Zining; Shan, Fei; Ying, Xiangji; Zhang, Yan; Li, Shuangxi; Jia, Yongning; Li, Ziyu; Ji, Jiafu (Frontiers in Oncology, 2020)
Background: The relationship between time to surgery (TTS) and survival benefit is not sufficiently demonstrated by previous studies in locally advanced gastric cancer (LAGC). This study aims to assess the impact of TTS after neoadjuvant chemotherapy (NACT) on long-term and short-term outcomes in LAGC patients. Methods: Data were collected from patients with LAGC who underwent NACT between January 2007 and January 2018 at our institution. Outcomes assessed were long-term survival, pathologic complete response (pCR) rate, and postoperative complications. Results: This cohort of 426 patients was divided into 5 groups by weeks of TTS. Under cox regression, compared to other groups, the 22-28 days and 29-35 days groups revealed a better OS (<21 vs 22- 28 days: HR 1.54, 95%CI=0.81-2.93, P=0.185; 36-42 vs 22-28 days: HR 2.20, 95%CI=1.283.79, P=0.004; 43-84 vs 22-28 days: HR 1.83, 95% CI=1.09–3.06, P=0.022) and PFS (<21 vs 22- 28 days: HR 1.54, 95%CI=0.81-2.93, P=0.256; 36-42 vs 22-28 days: HR 2.20, 95%CI=1.283.79, P=0.111; 43-84 vs 22-28 days: HR 1.83, 95%CI=1.09–3.06, P=0.047). Further analysis revealed a better prognosis in patients with TTS within 22-35 days (OS: HR 1.78 95%CI=1.252.54, P=0.001; PFS: HR 1.49, 95%CI=1.072.08, P=0.017). Postoperative stay was significantly higher in the <21 days group, while other parameters revealed no statistical significance (P>0.05). Restricted cubic spline depicted the nonlinear relationship between TTS and OS/PFS. Conclusion: Patients who received surgery within 35 weeks experienced the maximal survival benefit without an increase in postoperative complications or lowering the rate of pCR. Further investigations are warranted.